The objectives of this research were analyzing the performance of agricultural sector and agroindustry, relation between fiscal policy and performance of agricultural sector and agroindustry; analyzing fiscal policy instruments which were effective in influencing the agricultural sector performance and agroindustry performance, and relation between agricultural sector performance and agroindustry performance within fiscal condition of Indonesia. Data time series 1970.1 – 2005.5 were analyzed wi - Darsono .; Mangara Tambunan; Hermanto Siregar; D. S. Priyarsono (Forum Pasca Sarjana, 2008)
The objectives of this research were analyzing the performance of agricultural  sector and agroindustry, relation between fiscal policy and performance of agricultural sector and agroindustry; analyzing fiscal policy instruments which were effective in influencing the agricultural sector performance and agroindustry performance, and relation between agricultural sector performance and agroindustry performance within fiscal condition of Indonesia. Data time series 1970.1 – 2005.5 were analyzed with Vector Error Correction Model (VECM).  Research results showed that decrease in the performance of agriculture sector occurred in all aspects and its role in the economy, and the same phenomena occurred also in agroindustry.  Instruments of fiscal policy which in the long term affect strongly the performance of agricultural sector and agroindustry were budgets for the following: sector of agriculture, agricultural research and development, agriculture infrastructure, and fiscal decentralization. Performance respond of agricultural sector and agroindustry toward shock  of fiscal policy instruments, to achieve stability, took relatively long period (9 and 8 years respectively). Performance respond of agroindustry toward shock of agricultural sector, to achieve stability, took 6 years period.  Instruments of fiscal policy which were in the long term effective in improving  agricultural sector performance were value added tax, agriculture subsidy, budget for agriculture research and development, budget for agriculture infrastructure, and fiscal decentralization.  Instruments of fiscal policy which were in the long term effective in improving the performance of agroindustry were income tax, value added tax, budget for agriculture infrastructure, and fiscal decentralization.  Performance of agricultural sector which had roles in affecting the variability of agroindustry performance were GDP of agriculture, export and import of agricultural products. Key words:  fiscal policy, agricultural sector, agroindustry